Osteoporosis treatment in postmenopausal women with pre-existing fracture - Ming-Huei Cheng; Jung-Fu Chen; Jong-Ling Fuh; Wen-Ling Lee; Peng-Hui Wang (Elsevier, 2012)
Osteoporotic patients with existing fractures are at substantially higher risk of subsequent fractures than those free of fractures. Given the lack of head-to-head comparison trials, indirect comparison of various antiosteoporosis treatments may be an alternative way to develop a preliminary idea. The objective of this study is to conduct a systematic review of antiosteoporosis treatment clinical trials that have investigated on patients with existing fractures. All the results of randomized placebo-controlled trials of the available antiosteoporosis treatments, including bisphosphonates, selective estrogen receptor modulators, calcitonin, strontium ranelate, and agents derived from parathyroid hormone, on patients with existing fractures were summarized. All the antiosteoporotic agents had significant efficacy in increasing lumbar spine bone mineral density and reduction in the occurrence of any new vertebral fractures. All interventions provided gains in quality-adjusted life-years compared with patients without treatment. The results from an indirect comparison must be interpreted with caution due to heterogeneous study design, discrepancies of disease severity at baseline, and differences in analytical methodologies. The devastating complications subsequent to osteoporotic fractures create medical and financial burdens; therefore, treatment of patients with osteoporotic fractures should be positioned in the top priority in the utilization of medical resources.